Underground Galleried Building at Rennibister, Orkney - Marwick, Hugh (Proceedings of the Society of Antiquaries of Scotland, 1927)
A provisional account of the discovery of a hexagonal stone-built chamber with wall recesses and a passageway. The roof would have comprised overlapping stone slabs supported by four pillars. Quantities of disarticulated human bone were recovered from within the chamber. A brief note on the bones suggests they are mainly immature.